Предмет: Математика,
автор: arinabojko903
cos(a-b)-cos(a+b) =
Ответы
Автор ответа:
1
cos(a-b)-cos(a+b)= -2sin(a)*sin(-b)= -sin(a)*(-sin(b))= 2sin(a)*sin(b)
Автор ответа:
1
Ответ:
2sin(a)sin(b)
Пошаговое объяснение:
cos(a-b)-cos(a+b)= -2sin(a)sin(-b)= -2sin(a)×(-sin(b))=2sin(a)sin(b)
Похожие вопросы
Предмет: Другие предметы,
автор: ArinaKerzina1999
Предмет: Русский язык,
автор: nub241
Предмет: Русский язык,
автор: Суркова123
Предмет: География,
автор: Skavinastartitina
Предмет: Литература,
автор: 83Lera83